2019
DOI: 10.1186/s12870-019-2109-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a liverworts bHLH transcription factor involved in the regulation of bisbibenzyls and flavonoids biosynthesis

Abstract: BackgroundThe basic helix-loop-helix (bHLH) transcription factors (TFs), as one of the largest families of TFs, play important roles in the regulation of many secondary metabolites including flavonoids. Their involvement in flavonoids synthesis is well established in vascular plants, but not as yet in the bryophytes. In liverworts, both bisbibenzyls and flavonoids are derived through the phenylpropanoids pathway and share several upstream enzymes.ResultsIn this study, we cloned and characterized the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The differential accumulation of flavonoid-related metabolites in both passion fruit cultivars was not only related to enzymatic activity but also structural gene expressions. According to previous studies, it was also related to some transcription factors such as MYB [57], BHLH [58], and WD40 [59], regulation of microRNA during protein expression and, ubiquitination and phosphorylation during protein activation [60].…”
Section: Discussionmentioning
confidence: 95%
“…The differential accumulation of flavonoid-related metabolites in both passion fruit cultivars was not only related to enzymatic activity but also structural gene expressions. According to previous studies, it was also related to some transcription factors such as MYB [57], BHLH [58], and WD40 [59], regulation of microRNA during protein expression and, ubiquitination and phosphorylation during protein activation [60].…”
Section: Discussionmentioning
confidence: 95%
“…As well, many previous reports showed that flavonoids synthesized in plant could effectively eliminate ROS to enhance the tolerance in adverse environment ( Wang et al, 2016 ; Qin et al, 2020 ). Interestingly, some bHLHs were confirmed to be associated with flavonoids synthesis ( Zhao et al, 2019 ; Aslam et al, 2020 ) and belongs to subfamilies 2 ( Guan et al, 2013 ; Geng and Liu, 2018 ; Geng et al, 2019 ; Waseem et al, 2019 ; Zhao R. et al, 2020 ). Especially, experimental data showed that bHLHs bound to the promoter of antioxidant genes such as POD, SOD through E-box or G-box ( Liu et al, 2013 ; Geng and Liu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that multiple TFs regulate phenylpropanoid and flavonoid biosynthesis in plants. MYB ( Ma et al, 2018 ; Tang et al, 2021 ), bHLH ( Zhao et al, 2019 ), and WD40 ( Mol et al, 2021 ), ate the most important TFs, while NAC ( Yang et al, 2019 ), WRKY ( Joshi et al, 2022 ), and bZIP ( An et al, 2018 ) are the least important. In this study, 27 transcription factors that may play a role in the biosynthesis of phenylpropane or flavonoids were identified.…”
Section: Discussionmentioning
confidence: 99%